IMPLEMENTASI ERP DALAM PENGOLAHAN DATA ELEKTRONIK KAS GUNA MENUNJANG EFEKTIVITAS PENGENDALIAN INTERNAL PENERIMAAN KAS - Haryani, . (www.bsi.ac.id, 2015)
Each company implements systems and information technology to improve its competitiveness against other companies, as well as in terms of implementing Enterprice Resource Planning (ERP) as one solution. Still many companies are engaged in a trade or service companies that have not implemented information technology systems and well. In fact, there are still companies that have not entirely apply information systems. This is due to the still high cost of ERP implementation, complexity in the implementation of ERP, and complexity in the ERP maintenance, as well as other problems. To solve the problems above, needed a system and information technology as a solution. One of them is the solution to solve the problems in the financial management of a company. By using the accounting information system solutions offered to address financial management issues can be resolved properly. At this time PT. Bilanouv Brothers engaged in timber trading and leasing cargo aloes. Start of recording transactions, financial data processing to making the report is still not using accounting applications, making it possible during the process of recording took place there was an error and also made less accurate reports and delays in the search data - data that is required. To solve the existing problems in PT. Bilanouv Brothers used MYOB Premier v.12 application allows recording of financial transactions become more efficient and accurate report creation and fast. Is expected to use accounting application an activity that can be achieved effectively and efficiently in support of activities at PT. Bilanouv Brothers. Keywords: Enterprice Resource Planning, Internal Control Cash, MYOB